Effective? Locally owned? Beyond the technocratic perspective on the European Union Police Mission for the Palestinian Territories. Issue 1 (2nd January 2018) - Tartir, Alaa; Ejdus, Filip
ABSTRACT: The European Union Police Mission for the Palestinian Territories (EUPOL COPPS) was established in 2006 to contribute to the establishment of effective policing in support of an independent and democratic Palestinian state. EUPOL COPPS is often commended for its contribution to the professionalization of the Palestinian security sector under local ownership. Drawing on 40 interviews, we argue that the mission can be considered effective and locally owned only from a narrow technocratic perspective, which denies the political reality of continued occupation and absence of democracy. A broader analysis, which includes the voices of ordinary Palestinians, reveals that EUPOL COPPS contributed to the professionalization of authoritarian policing under continued Israeli occupation. Our findings show the limits of technocratic approaches to peacebuilding interventions and call for a stronger engagement with the ultimate beneficiaries of peacebuilding missions.